Rivalry USA and China in The Pacific: Interpretation of Communication Theorities - Joevi Roedyati; Hafied Cangara; Andi Faisal Bakti (Publikasi Indonesia, 2023)
Communication is a way of interacting with fellow human beings, because communication is essentially a needfor each individual to exist as a society. In communicating, ethics must be considered whencommunicating with others.Thisstudy aims to provide an overview of the perspectives and impressions exchanged by the United States and China during the Pacific War. Methods of the writings is qualitative, which sources are taken from many of Chinese and USA plus Australia and New Zealand’s policies in order to gain economic benefit from Pacific States. Superpowers have been put a lot of intentions in the Pacific regions, since its Colonial times. This writing only want to stressed the rivalty which had beenput in the region nowadays. This effort only tried to understand form of policies of the countries in the Pacific, to addressed these rivalries of ex colonial powers, USA and China, for least mentioned.